Determinasi Praktik Manajemen Laba pada Perusahaan Asuransi yang Terdaftar di Bursa Efek Indonesia - Syahliantia Yusika Sari; Nursiam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze and test the effect of profitability, financial leverage, company size, and cash holding on earnings management practices in insurance companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023. This study uses a quantitative approach with a purposive sampling method, resulting in 36 observation data from 12 companies that meet the criteria. The data were analyzed using multiple linear regression using the SPSS 25 program. The results showed that profitability, financial leverage, and cash holding had no significant effect. Meanwhile, company size has an effect on earnings management. These findings are expected to contribute to decision making by investors, company management, and further researchers.